Analysis And Formulation of Marketing Strategies in Third Party Logistics (3pl) to Increase Sales - Rodrick M. K. Sitompul (Management Institute Faculty of Economics Universitas Andalas, 2022)
Currently, the logistics business is one of the business sectors that has a high growth rate, this is in line with the increasing needs of people's lives accompanied by increasingly sophisticated technological developments. The Logistics Market in Indonesia in 2020 – 2024 shows a graph that continues to increase, meaning that the logistics business in Indonesia is always growing from year to year. ABC Company is the grandson of the Pertamina group and is a subsidiary of Pertamina Patra Niaga as a Commercial and Trading sub-holding. With this position, ABC is given the flexibility to do business with other sub-holdings but still in the corridor or core business in the logistics sector. Although the business that is targeted and engaged in still depends on the business potential of the parent company, in this case PT Pertamina group. However, ABC has not been able to capture the business potential that exists in the parent company because management does not get enough trust from the management of the parent company in managing work that is in accordance with the core/identity of ABC. Currently, the marketing strategy carried out by ABC is still not good. This can be proven by the fact that there is no other income and only depends on the operations of the parent company. There is no specific marketing strategy that can directly attract customers outside of the parent company PT. Pertamina is one of the reasons for the lack of income other than the parent company. In solving this problem, this study aims to formulate and analyze marketing strategies using external and internal analysis. Based on the results of the SWOT analysis, the company needs a strategy in the Defense category (W-T Combination) where the strategy is advertising, sales promotion, increasing focus on project channels and revitalizing the role of the HR Department.